2022
DOI: 10.3390/nano12081274
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Nanoformulation as a Carrier for Curcumin and pEGCG—Study on Stability and Anticancer Potential

Abstract: Nanoformulations are regarded as a promising tool to enable the efficient delivery of active pharmaceutical ingredients to the target site. One of the best-known and most studied nanoformulations are liposomes—spherical phospholipid bilayered nanocarriers resembling cell membranes. In order to assess the possible effect of a mixture of polyphenols on both the stability of the formulation and its biological activity, two compounds were embedded in the liposomes—(i) curcumin (CUR), (ii) a peracetylated derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…Liposomes were prepared according to a literature procedure [ 36 ] from 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP) mixture (8:2), and either CUR, BDMC, ORI, or ACT or their combination with the following molar ratio of 0.1:8:2 (CUR/ORI/ACT/BDMC:POPC:DOTAP), 0.05:0.05:8:2 (CUR:ORI:POPC:DOTAP), and 0.05:0.05:8:2 (ACT:BDMC:POPC:DOTAP). The final concentrations were as follows: 36.8 µg/mL CUR, 130.8 µg/mL BDMC, 44.8 µg/mL ORI, 62.5 µg/mL ACT, 6 080.6 µg/mL POPC, 1 397.1 µg/mL DOTAP and mixtures of compounds, respectively, 18.4 + 22.4 µg/mL CUR + ORI and 15.4 + 31.2 µg/mL BDMC + ACT.…”
Section: Methodsmentioning
confidence: 99%
“…Liposomes were prepared according to a literature procedure [ 36 ] from 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP) mixture (8:2), and either CUR, BDMC, ORI, or ACT or their combination with the following molar ratio of 0.1:8:2 (CUR/ORI/ACT/BDMC:POPC:DOTAP), 0.05:0.05:8:2 (CUR:ORI:POPC:DOTAP), and 0.05:0.05:8:2 (ACT:BDMC:POPC:DOTAP). The final concentrations were as follows: 36.8 µg/mL CUR, 130.8 µg/mL BDMC, 44.8 µg/mL ORI, 62.5 µg/mL ACT, 6 080.6 µg/mL POPC, 1 397.1 µg/mL DOTAP and mixtures of compounds, respectively, 18.4 + 22.4 µg/mL CUR + ORI and 15.4 + 31.2 µg/mL BDMC + ACT.…”
Section: Methodsmentioning
confidence: 99%
“…Incorporating polyphenolic compounds into liposomes can also enhance their stability. Some researchers discovered that embedding the polyphenolic compounds curcumin or/and EGCG into liposomes can increase their stability in blood circulation [ 145 ]. Moreover, these nanoformulations also possessed good anti-cancer performances in prostate cancer cells and bladder cancer cells [ 145 ].…”
Section: Progress In Nanocarrier-mediated Delivery Of Polyphenolic Co...mentioning
confidence: 99%
“…Some researchers discovered that embedding the polyphenolic compounds curcumin or/and EGCG into liposomes can increase their stability in blood circulation [ 145 ]. Moreover, these nanoformulations also possessed good anti-cancer performances in prostate cancer cells and bladder cancer cells [ 145 ]. Liposomes can also be applied for drug delivery in special physiological environments, such as the gastrointestinal environment.…”
Section: Progress In Nanocarrier-mediated Delivery Of Polyphenolic Co...mentioning
confidence: 99%
“…In a recent study, liposome synthesized from 1‐palmitoyl‐2‐oleoyl‐sn glycero‐3‐phosphocholine was utilized to increase the stability of the phytochemicals, which resulted in further increasing the stability of curcumin in co‐embedded in the nano‐liposome than curcumin encapsulated alone. The finding showed that the studied nanoformulation could be attended to for in vivo tests and used instead of dimethyl sulfoxide solvent in the in vitro tests (Piwowarczyk et al, 2022). Thus, targeted therapy based on liposomes could be a favorable vehicle to increase the concentration of related phytochemicals by careful delivery into cancer cells.…”
Section: The Anticancer Efficacy Of Single Polyphenols Plus Their Com...mentioning
confidence: 99%